การพัฒนาสื่อมัลติมีเดียเพื่อส่งเสริมทักษะและความเข้าใจของอาสาสมัครในการดูแลสุขภาพผู้สูงอายุในเขตเทศบาลเมือง จังหวัดลำปาง - บัวกนก ฟิสิกส์ ฌอณ (Area Based Development Research Journal, 2015)
บทคัดย่อไม่สมบูรณ์ The development of multimedia to enhance skill and understanding of volunteers in health care for elderly people in Lampang municipality, Lampang Province The purposes of this research were: 1) to develop the multimedia to enhance skill and understanding for volunteers in health care for elderly people in Lampang municipality, Lampang province 2) to study the learning achievement of volunteers in health care for elderly people after using the multimedia 3) to study the components of multimedia production to enhance skill and understanding for volunteers in health care for elderly people. The multimedia produced by the research team were used to test the sampling group including 60 volunteers. The experimental design was One - shot case study. The results from the test were used to assess the efficiency of the multimedia. Learning Achievement Test, both theory and practice, was conducted after the using of multimedia among the sampling group. Finally, the media production team was interviewed to find out the elements of multimedia production to enhance skill and understanding for volunteers in health care for elderly people. The results were as follows: 1. The computer multimedia had efficiency criterion of 84.44/84.22 which was higher than the selected efficiency criterion of 80/80. 2. The learning achievement of multimedia meets the criteria defined. 80 percent of volunteers had scored 70 percent or more. The average grade totals 74.90 was good. 3. Components of the multimedia production from the study had 3 steps: Planning, Design and Development. 5 elements of multimedia program to enhance skill and understanding for volunteers in health care for elderly people were: Introduction of the program, Learner control, Presentation of information, Helping, and the End of the program.